2017
DOI: 10.15835/nbha45210826
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Rootstock on the Growth and Fructification of Cherry Cultivars in a High Density Cultivation System

Abstract: The influence of rootstock on the growth and fruiting of three sweet cherry cultivars ('Bigarreau Burlat', 'Kordia', 'Regina') was studied under the pedoclimatic conditions of Cluj-Napoca, Romania, in 2014-2016. The trees were grafted on Gisela 5 rootstock, trained as Zahn Spindle and the orchard had a density of 1666 trees/ha. Root were cut twice, at 50 cm distance from the trunk, in an angle of 45° and 30 cm depth, as followed: first time, to the autumn, in fall leaves time, on one side of the row and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…In addition to growth, many agronomically desirable qualities are also influenced by the pattern of stock-scion interaction. Pal et al (2017) established that rootstock has a pronounced effect on growth as well as fructification in cherry. Lesser number of fruiting branches were formed in trees grafted on Mahaleb than those grafted on "Gisela 5."…”
Section: Effect Of Rootstock-scion Interaction On Growth Quality Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to growth, many agronomically desirable qualities are also influenced by the pattern of stock-scion interaction. Pal et al (2017) established that rootstock has a pronounced effect on growth as well as fructification in cherry. Lesser number of fruiting branches were formed in trees grafted on Mahaleb than those grafted on "Gisela 5."…”
Section: Effect Of Rootstock-scion Interaction On Growth Quality Andmentioning
confidence: 99%
“…In addition to growth, many agronomically desirable qualities are also influenced by the pattern of stock-scion interaction. Pal et al (2017) established that rootstock has a pronounced effect on growth as well as fructification in cherry. Lesser number of fruiting branches were formed in trees grafted on Mahaleb than those grafted on “Gisela 5.” A comparative evaluation of the two rootstocks indicated that fruit yield was almost double where “Gisela 5” was used as a rootstock compared to Mahaleb, in the first 3 years of fruiting.…”
Section: Effect Of Rootstock-scion Interaction On Growth Quality Andmentioning
confidence: 99%
“…However, the same plant might perform surprisingly poorly when planted under certain conditions, while able to thrive in an alternative condition. Sweet cherry trees grafted on 'Gisela 5' have shown good performance when irrigated (Pal et al, 2017), but the same was not observed under the drought (Vercammen, 2004). In our study, significantly higher V e and k h(T) of trees grafted on P. cerasus, in comparison with the trees on 'Gisela 5', showed better adaptation of these rootstock candidates in the trial without irrigation implemented.…”
Section: Discussionmentioning
confidence: 99%
“…If the rootstock is chosen for its ability to grow strong, persistent root systems in the particular soil, scions are selected primarily for the quality and quantity of their fruits (Cohen and Naor, 2002). The effect of rootstock selection on sweet cherry yield and fruit quality was investigated through many studies (Santos et al, 2006;Wociór, 2008;López-Ortega et al, 2016;Dziedzic et al, 2017;Pal et al, 2017;Morandi et al, 2019). Concerning the changing climate that seriously affects fruit growth and yields, rootstocks investigation must be focused on vigour-controlling genotypes with high adaptability to soil water limitations, considering specific pedo-climatic conditions of the area (Ljubojević et al, 2017(Ljubojević et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The suitability of cultivar-rootstock combinations to local climate conditions, together with soil properties and growing technologies, is one of the key factors in sweet cherry production (Pal et al, 2017). In the last two decades, the new dwarfing and semi-dwarfing cherry rootstocks have allowed obtaining high fruit yields of satisfactory quality.…”
Section: Introductionmentioning
confidence: 99%